PUBLIC SECTOR REFORM AND PUBLIC ACCOUNTABILITY IN NIGERIA: A STUDY OF INTEGRATED PERSONNEL PAYROLL AND INFORMATION SYSTEM - Nnamani, Kelechi; Ochiaka, Dorothy; Eze, Beatrice; Nwoke, Ikemefuna (University of Nigeria Journal of Political Economy, 2021)
One of the major features of the democratization processes in Nigeria is the implementation of several reforms aimed at addressing the institutional and structural malfeasance occasioned by the long presence of military rule. Among many of these reforms is the World Bank-guided Integrated Personnel Payroll and Information System (IPPIS) principally targeted at enhancing accountability in the public sector. As a corollary, this study evaluated the efficacy of the Integrated Personnel Payroll and Information System in minimizing sharp practices in Nigeria. We utilized the basic propositions emanating from the Structural-Functional theory while data for the study were elicited primarily through the aid of the questionnaire. Based on the information generated, we found that the implementation of the Integrated Personnel Payroll and Information System has reasonably check-mated the corrupt-ridden public sector in Nigeria. In view of the finding, the study recommended that the federal government should ensure the integration of all workers under her payroll into the system. We further maintained that the other levels of government should tread the path of the federal government to ensure that the high incidence of corruption is minimized to the barest minimum in Nigeria.